KUALITAS KEPEMIMPINAN, KOMUNIKASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT VINSA MANDIRA UTAMA SUKOHARJO - Erma Ayuningtyas; Sri Hartono; Eny Kustiyah (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This study aims to determine and describe the influence of leadership quality, communication and motivation simultaneously or persially on the performance of employees of PT Vinsa Mandira Utama Sukoharjo. This research uses quantitative descriptive. The number of samples used was 65 respondents. The sampling method uses accidental sampling. The questionnaire is used for sampling. The data analysis technique used is statistical analysis, using SPSS version 22, with quantitative analysis which includes validity and reliability tests, classic assumption tests, multiple linear regression analysis, hypothesis testing with F test and t test and coefficient of determination. The results of this F test indicate that the quality of leadership, communication and motivation simultaneously and significantly influence the performance of employees of PT Vinsa Mandira Utama Sukoharjo. T test results indicate that the quality of leadership and communication has a positive and significant effect on performance while motivation has a negative and not significant effect on the performance of employees of PT Vinsa Mandira Utama. The coefficient of determination shows that leadership, communication and motivation variables have a 55% influence on the performance of employees of PT Vinsa Mandira Utama Sukoharjo.